The Jewish annotated New Testament : New Revised Standard Version Bible translation - Levine, Amy-Jill, 1956-; Brettler, Marc Zvi. (Oxford, Oxford University Press, 2011)
The intention for publishing The Jewish Annotated New Testament, according to its editors, Amy-Jill Levine and Mark Zvi Brettler is to recognize the growing understanding between Jewish and Christian traditions, and to help further that understanding. The editors of this volume, both distinguished New Testament scholars, had two key reasons for creating this "Jewish Annotated New Testament." First they wanted Christian readers to learn more about the Judaic origins of Christianity and the context surrounding the life of Jesus. Second, they wanted to introduce Jewish readers to what is unquestionably one of the canonical texts in Western Civilization, whether they believe in it or not. Many of the glosses found in the text are geared at linking the ideas and events of the gospels to their background in the history of Judaism. Each of the books of The New Testament is accompanied by a brief introductory essay. There are also a number of shorter sidebar essays positioned within each book to help to explain specific passages at greater length. Finally the end of the book contains a number of essays by leading experts on the Bible and Jewish history on a broad range of relevant topics
Includes bibliographical references (pages 601-602) and index
The New Revised Standard Version Bible translation is based "on the most recent edition of the Greek New Testament ... published by the United Bible Societies (1966)"--Page xvii
Keywords: Bible. -- Commentaries; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc., Jewish; Judaism; Jews in the New Testament; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Commentaries; Criticism, interpretation, etc